+0  
 
0
238
2
avatar

(-2x)^-2 How is this broken down?

Guest Oct 23, 2017
edited by Guest  Oct 23, 2017
edited by Guest  Oct 23, 2017
 #1
avatar
+2

Simplify the following:
(-2 x)^(-2)

 

Multiply each exponent in -2 x by -2:
(1)/((-2)^2 x^2)

 

(-2)^2 = 4:
 1/(4 x^2)

Guest Oct 23, 2017
 #2
avatar+7339 
+1

Also remember

 

\((-2x)^{-2}\,=\,\frac{1}{(2x)^2}\,=\,\frac{1}{(2x)(2x)}\,=\,\frac{1}{2\cdot x\cdot 2\cdot x}\,=\,\frac{1}{2\cdot2\cdot x\cdot x}\,=\,\frac{1}{4x^2}\)

hectictar  Oct 23, 2017

17 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.